Evaluación de la actividad antifúngica del extracto total de una especie de la familia Ericaceae sobre el agente etiológico Neopestalotiopsis javaensis - Ruano Pérez, Josué David (2022)
Worldwide, avocado consumption has been on a growing trend in recent years, which is why its production has increased in Ecuador\; however, the quality of the product has been affected mainly by the appearance of the disease known as 'scab'. In order to find alternatives to this problem, plant extracts have been used that have antifungal activity and, in turn, offer alternatives to the use of synthetic fungicides and reduce environmental pollution. The main objective of this research was to evaluate the antifungal activity of the total extract of the plant species Pernettya prostrata belonging to the Ericaceae family on the etiological agent Neopestalotiopsis javaensis. In order to achieve the objective, the plant was collected in the Cuicocha Lake, which was subjected to a dehydration process to obtain the total extract through the dynamic maceration process using methanol as a solvent. It was evaluated at four serial concentrations of 500, 250, 125 and 62.5 mg/ml following the Kirby-Bauer methodology of direct diffusion in agar on the previously isolated etiological agent Neopestalotiopsis javaensis. A total extract of Pernettya prostrata was obtained with a yield of 31.48%\; however, the four concentrations of the total extract of Pernettya prostrata did not show activity antifungal against the etiological agent under study.